Site selection analysis of radio monitoring stations to BDS based on STK orbital prediction data - Qi ZHANG; Hui LIN (Dianxin kexue)
BeiDou navigation satellite system (BDS) is a global navigation satellite system constructed and operated by China.At present,BDS is able to provide location,navigation and time service in Asia-Pacific,and will provide global service in 2020 as planned.As the fact of the rapid development of satellite communication technology,the spectrum and orbits of satellite are increasingly crowed.Therefore,it is vital to perform spectrum monitoring to BDS.Based on the STK orbital prediction data,the access time of the 14 non-GEO satellites in BDS to 9 Chinese cities in 10 days was collected.Group analysis according to different satellites and different cities,and similarity analysis within different cities were performed using the R programming language.At last,preliminary advices on site selection were provided according to the data analysis results.